A robot control architecture supported on contraction theory. Issue 1 (2nd January 2017) - Silva, Jorge; Sequeira, João; Santos, Cristina
ABSTRACT: This paper proposes fundamentals for stability and success of a global system composed by a mobile robot, a real environment and a navigation architecture with time constraints. Contraction theory is a typical framework that provides tools and properties to prove the stability and convergence of the global system to a unique fixed point that identifies the mission success. A stability indicator based on the combination contraction property is developed to identify the mission success as a stability measure. The architecture is fully designed through C 1 nonlinear dynamical systems and feedthrough maps, which makes it amenable for contraction analysis. Experiments in a realistic and uncontrolled environment are realised to verify if inherent perturbations of the sensory information and of the environment affect the stability and success of the global system.